THE INCREASE OF STUDENTS' ARABIC READING SKILLS THROUGH THE APPLICATION OF SQ4R LEARNING TECHNIQUE - Erlina, Nova (IJLECR (International Journal of Language Education and Cultural Review), 2018)
The aim of this research is to increase the Arabic reading skills of the students in the forth semester of the Department of Arabic Language Education, Academic Year 2017 in understanding Arabic texts through the application of SQ4-R learning technique. This research is an action research with qualitative approach. Methods for data gathering: observation, interview, portfolio, reading comprehension test, and field record. Data were analyzed qualitatively by reducing and presenting them as well as withdrawing conclusion. Research findings: The application of SQ4-R endured modification through the addition of a learning stage, namely stage on finding vocabulary and meaning in dictionary that happened post survey stage. Through this action research, SQ4-R was modified into SVQ4-R. The result of this research shows increase on the students’ skills in which initially they simply reached literal comprehension with class’ average score 48 prior to the action, 69.7 in the 1st cycle, 77.68 in the 2nd cycle, and 78.22 in the 3rd cycle. The average score on interpretative comprehension, prior to the action, did not appear, in the 1st cycle, 67, in the 2nd cycle 68.4, and in the 3rd cycle, 73. The average score on applicative and critical comprehension, prior to the action did not appear in the 1st cycle, 64.3, in the 2nd cycle, 70.4, and in the 3rd cycle, 78.09.